The South-South partnership to provide cardiac surgery: The Namibian Children Heart Project - Shidhika, Fenny Fiindje (Department of Paediatrics and Child Health, 2019)
Introduction: Congenital and acquired heart diseases are highly prevalent in developing countries despite limited specialised care. Namibia established a paediatric cardiac service in 2009 with significant human resource and infrastructural constraints. Therefore, patients are referred for cardiac interventions to South Africa. Objectives: To describe the diagnoses, clinical characteristics, interventions, post-operative morbidity and mortality and follow-up of patients referred for care. Methods: Demographics, diagnoses, interventions, intra- and postoperative morbidity and mortality as well as longitudinal follow-up data of all patients referred to South Africa were recorded and analysed. Results: The total cohort constituted 193 patients of which 179 (93%) had congenital and 7% acquired heart disease. The majority of patients (78.8%) travelled more than 400 km to Windhoek prior to transfer. There were 28 percutaneous interventions. Palliative and definitive surgery was performed in 27 and 129 patients respectively. Eighty (80/156, 51.3%) patients had postoperative complications, of which 15 (9.6%) were a direct complication of surgery. Surgical mortality was 8/156 (5.1%, 95% confidence interval 1.2.2-9.8), with a 30- day mortality of 3.2%. Prolonged ICU stay was associated with a 5% increased risk of death (Hazard Ratio 1.05, 95% confidence interval: 1.02-1.08, p=0.001). Follow-up was complete in 151 (78%) patients over seven years. Conclusions: Despite the challenges associated with a cardiac programme referring patients for intervention to a neighbouring country and the adverse characteristics of multiple lesions and complexity associated with late presentation, we report good surgical and interventional outcomes. Our goal remains to develop a comprehensive sustainable cardiac service in Namibia.